Hypertonic saline versus fluid restriction: The pitfalls in managing acute hyponatremia in a patient with long‐standing spinal cord injury. Issue 12 (2nd December 2022) - Koutroukas, Vaios; Pavlou, Panagiotis; Smith, Emilia Imogen; Ciutac, Andra Maria; Redford, Christopher; Smith, Jamie C.
Abstract: Spinal cord injury‐induced hyponatremia is an under‐recognized entity, without a mention in the European hyponatremia guidelines. We present a case of a 56‐year‐old female quadraplegic patient with cervical cord injury, presenting with severe hyponatremia and tonic–clonic seizures. This case highlights the challenges in medical management; action mechanisms are further discussed. Abstract : In patients with spinal cord injury‐induced hyponatremia, it is important to maintain a careful fluid balance to allow adequate intake but avoid over‐hydration, backed up by judicious monitoring of electrolytes.